Perilaku Individu dalam Lembaga Pendidikan Islam - Khoirunnisaa' Khoirunnisaa'; Sulistiyorini Sulistiyorini (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
The study of aspects of human behavior in a particular group which includes aspects caused by the influence of organizations on humans as well as human influences on organizations including organizational behavior. There are two factors that influence individual behavior towards Islamic educational institutions, namely internal and external factors. Internal factors include heredity (heredity or innate). External factors include the environment, maturity or experience and education. While the individual behavior analysis variables include psychological, physiological and environmental variables. Psychological variables include perceptions, personality attitudes, learning and motivation. Physiological variables include physical abilities and mental abilities. And environmental variables include family, culture and social class. As an initial understanding to be able to understand individual behavior well, it is necessary to understand the characteristics inherent in individuals which include biographical characteristics, personality, perceptions and attitudes. The verses of the Qur'an relating to individual behavior form the basis that Islamic educational institutions have hinted that humans have positive and negative potentials in behavior, and in essence the positive potential of humans is stronger than their negative potential.